2017
DOI: 10.1002/mnfr.201700313
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Grifola frondosa polysaccharides improves memory impairment in aged rats via antioxidant action

Abstract: These findings indicated that oral administration of GFP could improve memory impairment via antioxidant action, and dietary supplementation with GFP may provide potential benefits on brain aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Grifola frondosa polysaccharide-N (GFP-N) also demonstrated hypoglycemic effects in diabetic mouse livers [81]. GFP administration also significantly improved memory impairment in aged rats via antioxidant action, thus can be a good dietary supplement for brain aging [80].…”
Section: Mushroom Species Containing Bioactive Polysaccharidesmentioning
confidence: 99%
“…Grifola frondosa polysaccharide-N (GFP-N) also demonstrated hypoglycemic effects in diabetic mouse livers [81]. GFP administration also significantly improved memory impairment in aged rats via antioxidant action, thus can be a good dietary supplement for brain aging [80].…”
Section: Mushroom Species Containing Bioactive Polysaccharidesmentioning
confidence: 99%
“…With an increase in the global population and extension of lifespan, aging is becoming one of the most important public health issues (Chen et al, 2017). Aging is a known major risk factor in many human diseases such as cancer, idiopathic Parkinson's disease, type I and II diabetes, cardiovascular disease, and metabolic syndrome (Barzilai et al, 2012;Dillin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, decreases in cognitive function were demonstrated to severely impact the quality of life of patients ( 45 ). Although effective interventions to address these impairments and their underlying mechanisms remain to be identified ( 3 , 46 ), accumulating evidence has suggested that neuroinflammation in the brain may play a vital role in the pathophysiology of cognitive decline ( 47 ). To determine whether the anti-inflammatory properties of LBP exerted a protective effect against neurodegenerative disease, an OVX-induced cognitive impairment in vivo model was established, which is widely accepted as an experimental model for the study of neurodegenerative diseases ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is a complex process characterized by a progressive loss of functions; in particular, learning and memory impairments (1). In women, decrease in estrogen levels is an important component of the aging following menopause, and brain and endocrine aging occur simultaneously and are closely associated with cognitive impairment and pathological states (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%